Dynamic capacity management for healthcare : Advanced methods and tools for optimization - Story, Pierce (Boca Raton [Fla.] : CRC Press, 2011)
"Presenting new approaches, tools, and perspectives, this book facilitates the effective management of the complexities and "dynamism" unique to health care operations. It introduces healthcare managers and professionals to state-of-the-art concepts designed to improve both process- and dynamic systems-focused performance and develop appropriately dynamic process-level solutions to complex systems level issues. Employing common methodologies such as Lean, Sigma Six, and CQI, the "Dynamic Capacity Management" approach addresses the analysis and improvement of hospital- and department-wide capacity, patient flow, resource allocation, and performance optimization" - Provided by publisher.
Introduction ; Variability: killer of capacity ; Interdependencies ; DCAMM introduction ; Predictive analytics ; Demand components: the emercency department ; Surgical services and DCAMM analytics ; Up-down-up: creating a systems view from a component perspective ; Capacity patterns and analytics for DCAMM ; Dynamic resource allocations, dynamic standardization, and workload analytics ; A word on mandated nurse-patient ratios ; Outlier management and system balance.
"A Productivity Press book".
Includes bibliographical references and index.
Keywords: Hospitals -- Administration; Hospital Administration -- methods -- United States; Efficiency, Organizational -- United States; Health Services Needs and Demand -- organization & administration -- United States; Hospital Bed Capacity -- United States; Organizational Innovation -- United States; Quality of Health Care -- organization & administration -- United States